Section3

Section3 - Chapter 3. Di ff erentiation 3.3 Di ff...

Info iconThis preview shows pages 1–3. Sign up to view the full content.

View Full Document Right Arrow Icon

Info iconThis preview has intentionally blurred sections. Sign up to view the full version.

View Full DocumentRight Arrow Icon
This is the end of the preview. Sign up to access the rest of the document.

Unformatted text preview: Chapter 3. Di ff erentiation 3.3 Di ff erentiation Rules Derivative of a Constant Function. If f has the constant value f ( x ) = c , then df dx = d dx [ c ] = 0 . Proof. From the definition: f ( x ) = lim h f ( x + h )- f ( x ) h = lim h o c- c h = lim h 0 = 0 . QED Power Rule for Positive Integers If n is a positive integer, then d dx [ x n ] = nx n- 1 . Note. Before we present the proof of the Power Rule, we introduce the Binomial Theorem. Theorem. Binomial Theorem Let a and b be real numbers and let n be a positive integer. Then ( a + b ) n = a n + na n- 1 b + n ( n- 1) 2 a n- 2 b 2 + . . . + nab n- 1 + b n = n i =0 n i a n- i b i where n i = n ! ( n- i )! i ! and i ! = ( i )( i- 1)( i- 2) (3)(2)(1) . Note. We can prove the Binomial Theorem using Mathematical Induc- tion ....
View Full Document

Page1 / 4

Section3 - Chapter 3. Di ff erentiation 3.3 Di ff...

This preview shows document pages 1 - 3. Sign up to view the full document.

View Full Document Right Arrow Icon
Ask a homework question - tutors are online